2004
DOI: 10.1021/ja048862d
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Dispersion Polymerization toward Monodisperse, Controlled Micrometer-Sized Copolymer Particles

Abstract: We describe a two-stage dispersion polymerization process to prepare monodisperse micrometer-sized polymer particles in which problematic reagents, such as functional monomers and cross-linkers that commonly disrupt the particle-forming process, were added to the reaction after the nucleation stage was complete. Comonomers added after this point became incorporated into the particles without disturbing the final particle size and size distribution. In this way dye-labeled or functional group-containing microme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
168
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(173 citation statements)
references
References 16 publications
1
168
1
Order By: Relevance
“…7(D)), resulting in porous particles. The reason that the crosslinker should be introduced later is well explained by Winnik et al [64] They reported that crosslinkers and polar monomers significantly influence the particle growth and the monodispersity may be lost in such cases. The most important stage for the monodispersity of final particles was found to be the nucleation step.…”
Section: Dispersion Polymerizationmentioning
confidence: 95%
See 1 more Smart Citation
“…7(D)), resulting in porous particles. The reason that the crosslinker should be introduced later is well explained by Winnik et al [64] They reported that crosslinkers and polar monomers significantly influence the particle growth and the monodispersity may be lost in such cases. The most important stage for the monodispersity of final particles was found to be the nucleation step.…”
Section: Dispersion Polymerizationmentioning
confidence: 95%
“…The crosslinker should be added only after the nucleation stage ( Fig. 7(C)), which corresponds to less than 1% monomer conversion [64]. By the addition of crosslinker, porogen swollen particles continue to grow and crosslink ( Fig.…”
Section: Dispersion Polymerizationmentioning
confidence: 99%
“…28,29 Choe and coworkers 113 have reported that RAFT dispersion polymerization of S in ethanol at 70 C results in phase separation (a pink coagulant at the bottom of the reactor) when the RAFT agent is charged at the beginning of the polymerization. However, use of the two-stage method, [114][115][116] whereby the RAFT agent is added after the particle nucleation has been completed, results in good control/livingness without phase separation as well as a narrow particle size distribution. It cannot be stated with certainty whether the scCO 2 /MMA RAFT dispersion polymerization 28,29 proceeds satisfactorily without application of the two-stage method due to the characteristic features of scCO 2 (e.g., low viscosity, high diffusivity, etc.).…”
Section: Dispersion Raft Polymerization In Supercritical Comentioning
confidence: 99%
“…68 However, the addition of CLRP reagents (e.g., RAFT agent) leads to a marked broadening of the distribution. [114][115][116]138 In the dispersion polymerization of MMA in scCO 2 at 65 C using a PDMS stabilizer, the addition of a RAFT agent led to a slight reduction in particle diameter from $4.0 lm to 1.4 lm, and a broadening in the particle size distribution. The conversion range over which nucleation (particle formation) occurs is the most important factor-a short nucleation stage is required for a narrow particle size distribution.…”
Section: Particle Shape and Particle Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation